On Analysis and its Role in Communication Theories - Marton Demeter (KOME: An International Journal of Pure Communication Inquiry, 2012)
This paper tries to show that framing a propedeutics for a givendiscipline necessarily presupposes some so-called analytical movements with which the conceptual frame of the discipline could be related to itself, and to other disciplines as well. The situation is the same with communication studies, where, as this paper proposes, many of the so-called axioms of human communication should have been analyzed. After explicating the main types of analysis, the discussion tries to apply its analytical methods on Watzlawick’s first axiom of human communication, and tries to show, that the statement that ’one cannot not communicate’ is either false or meaningless.